2020
DOI: 10.1039/c9tb02341k
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-stabilized manganese-based nanocomposites with sensitive tumor microenvironment responsivity and their application for efficient SiRNA delivery in brain tumors

Abstract: Synthesis of Mn(iii)/Mn(iv) integrated nanocomposites to realize sensitive MRI performance in weakly acidic environments and efficient siRNA delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Fluorescence spectroscopic analysis of BSA after treatment with graded Mn 2+ concentrations showed that the BSA-characteristic emission at 336 nm gradually decreased with increasing Mn 2+ feeding ratios (Fig. 2g ), which was ascribed to the binding between Mn 2+ and aspartic acid or histidine residues in BSA and consistent with the observations in previous reports 34 36 . According to the DLS analysis, the hydrodynamic size of BSA-Man@Mn 2+ was around 8 nm in aqueous solution (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Fluorescence spectroscopic analysis of BSA after treatment with graded Mn 2+ concentrations showed that the BSA-characteristic emission at 336 nm gradually decreased with increasing Mn 2+ feeding ratios (Fig. 2g ), which was ascribed to the binding between Mn 2+ and aspartic acid or histidine residues in BSA and consistent with the observations in previous reports 34 36 . According to the DLS analysis, the hydrodynamic size of BSA-Man@Mn 2+ was around 8 nm in aqueous solution (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, the designed NPs showed minimal toxicity against normal human astrocytes [ 173 , 174 ]. Another recent study reported the enhancement of metallic NPs stability in siRNAs delivery and glioblastoma treatment via decoration with albumin [ 175 ]. In this regard, bovine serum albumin-stabilized manganese-based NPs were fabricated to efficiently deliver VEGF-siRNAs in brain tumor treatment.…”
Section: Modern Rna-based Therapeutic Modalitiesmentioning
confidence: 99%
“…Mn(iii) and Mn(iv) integrated nanocomposites were prepared with good stability and excellent biocompatibility. These NPs show superior advantages of siRNA delivery in gliomas, including increasing tumor uptake, improving tumor accumulation, and enhancing the therapeutic effect by adjusting TME (Xu et al, 2020).…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%